Bentuk Kesiapsiagaan Menghadapi Bencana Alam Banjir Bandang Suku Wana, Kabupaten Morowali Utara, Sulawesi Tengah - Utami, Rosan Cahya; Tyas, Wido Prananing (Jurnal Pembangunan Wilayah dan Kota, 2021)
Flood is the most frequent natural disaster in North Morowali, Central Sulawesi Province, Indonesia. The local government has tried to formulate disaster risk reduction plan to overcome this problem, but its implementation is not involves the local Â capacity. On the other hand, the Morowali local community, especially the Wana tribe, have been implementing disaster preparedness based on their own culture. The purpose of this study is to identify flood and flash-flood disaster preparedness activities of the Wana Tribe using ethnographic approach. By using the ethnographic approach, disaster preparedness activities in the Wana tribe can be comprehensively described, so they can be a valuable lessons related to cross-stakeholder Disaster Risk Reduction Program formulation. The study was a qualitative study using field observations, interviews, and literature review as the data collection method. The results showed that Wana Tribe had various disaster preparedness activities, which met the ideal disaster preparedness practices according to literature. These activities include: early warning system through the nature sensing, evacuation facilities provisioning, community based resource sharing, logistics provisioning, timely monitoring of flood hazards through river fringing, and all of them are applied in every authority level, either in the individual, family, neighborhood or village level.